Structural Model Presentation of Psychological Maladjustment Based on Post-Traumatic Stress Symptoms with the Mediating Role of Ego Strength in Individuals with Chronic Pain - Gholami Gharahchenagh, Khadijeh; Haghayegh, Seyed Abbas; Jabalameli, Sheida; Raeisi, Zohreh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to present a structural model of psychological maladjustment based on post-traumatic stress symptoms with the mediating role of ego strength in individuals suffering from chronic pain. Methods: The research method was descriptive, correlational, and structural equation modeling was used. The study population included all patients suffering from chronic pain who had visited specialized pain clinics in Tehran from February 2021 to May 2021. Using the Tabachnick and Fidell (2007) formula, the sample size was determined to be 330, selected through convenience sampling. Research instruments included the Psychological Adjustment Questionnaire (Rohner & Khaleque, 2005), the Mississippi Scale for Post-Traumatic Stress Disorder (1998), and the Psychological Ego Strength Scale (Markstrom et al., 1997). Data analysis was conducted in two parts: descriptive (central and dispersion indices, skewness, and kurtosis) and inferential (structural equation modeling) using SPSS-V23 and LISREL-V8.8 software. Findings: The results indicated that the model has a good fit. Additionally, the results showed that there is a significant direct and indirect relationship (mediated by ego strength) between post-traumatic stress and psychological maladjustment in individuals with chronic pain. The results suggest that the effect of post-traumatic stress indirectly influences psychological maladjustment positively through ego strength, with a magnitude of 0.81. Conclusion: Therefore, through individual and group therapy sessions, assistance should be provided to patients with chronic pain suffering from post-traumatic stress disorder symptoms, enabling them to fairly assess their functioning in life, free the individual from potential guilt at the time of the incident, and the lack of positive individual performance. Thus, by increasing ego strength and reducing avoidance behaviors, a lesser degree of psychological maladjustment can be expected in the individual.